Pengaruh Pengetahuan Produk dan Persepsi Kualitas terhadap Niat Beli Mobil Datsun Go Panca - Aditya Rian Firmansyah (BISMA (Bisnis dan Manajemen), 2018)
This study aims to investigate and discuss the influence of knowledge and perception of the quality of the product purchase intentions Datsun Go Panca.The sampling technique used is non - probability sampling and sampling conducted by judgmental sampling with a sample taken as many as 210 people. The target populationis the respondents whowere visitinga car show LCGC especially Datsun Go Panca.The scale of measurementin this study using a Likert scale. Measuring instrument usedwas a questionnaire. Analysis of data using multiple linear regression model. The results showedthat the effectof product knowledge on the intentionto buy Datsun Go Panca and influence the quality perception and purchase intent Datsun GoPanca, contributed 49.5%.